High performance tubular protonic ceramic fuel cells via highly-scalable extrusion process. (5th August 2021) - Zhu, Liangzhu; O'Hayre, Ryan; Sullivan, Neal P.
Abstract: We report an effective method to fabricate long, anode-supported tubular protonic ceramic fuel cells (PCFCs) and test cells in single-cell and short-stack mode. Further, we use our tubular PCFC platform to directly compare three high performance cathodes reported in literature: BaCo0·4 Fe0·4 Zr0·1 Y0·1 O3-δ (BCFZY), Ba0·5 Sr0·5 Co0·8 Fe0·2 O3-δ (BSCF), and PrBa0.5 Sr0·5 Co1·5 Fe0·5 O6-δ (PBSCF) using indentical preparation methods, which can minimize effects from variation of materials either due to suppliers or subsequent processing and testing from different research labs. Using a BCFZY cathode, the maximum power density of our tubular PCFC reaches 164, 308, and 517 mW cm −2 at 500, 550, and 600 °C, respectively. A 2-cell tubular short stack provides a total power of 2.3 W at 600 °C with tube diameters of 0.82 cm and a total tube active length of 3.2 cm. At 600 °C, the maximum power density reaches, 534, 517, and 326 mw cm −2 for the BSCF, BCFZY, and PBSCF cathodes, respectively. Under the same conditions, the BSCF-based cell shows the lowest total resistance mostly due to the lowest ohmic resistance and modest polarization resistance. The BCFZY-based cell has the lowest polarization resistance but larger ohmic resistance leading to a slightly higher total resistance than BSCF. The PBSCF cell has an ohmic resistance close to BSCF but a total polarization resistance much larger than either BSCF or BCFZY cell which results in the lowest overall performance. Highlights: Up to 66 cm long straight green PCFC anode supports are extruded. Tubular PCFC cells with dense electrolyte layer are fabricated. Three emerging PCFC cathode materials, BSCF, BCFZY, and PBSCF are synthesized and compared. Maximum power density exceeds 500 mW cm −2 at 600 °C using BCFZY and BSCF cathodes. A short 2-cell stack delivers 2.3 W power output at 600 °C.